Representations of Discrimination Against the Descendants of Former Political Prisoners: A Novel Study from the Perspective of Gramsci's Hegemony - Fadhila Nur Usman; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the representation of discrimination against the descendants of former political prisoners in Leila S. Chudori's novel Namaku Alam using Antonio Gramsci's hegemony theory. This study focuses on revealing how ideological power operates through culture, hegemony, ideology and popular belief (common sense), the role of intellectuals, and the state as reflected in literary texts. This study uses a qualitative descriptive method with a sociology of literature approach that views literary works as a reflection of the social and ideological realities of society. The research data comes from narrative excerpts, dialogues, and situational descriptions in the novel Namaku Alam obtained using documentation guidelines. Data analysis was conducted using content analysis techniques to interpret ideological messages and power relations in the text. The results show that this novel represents the practice of discrimination against the descendants of former political prisoners through five main forms. First, the cultural aspect displays the legacy of stigma. Second, the hegemonic aspect shows the dominance of state ideology through educational institutions. Third, the ideological and common sense aspects are seen through symbolic terms such as